2020
DOI: 10.3390/geosciences10080297
|View full text |Cite
|
Sign up to set email alerts
|

Reinterpreting Models of Slope-Front Recharge in a Desert Basin

Abstract: Identification of recharge areas in arid basins is challenging due to spatial and temporal variability and complexity of the hydrogeology. This study re-evaluates recharge mechanism in a desert basin where isotopic and geologic data indicated that published conceptual models of recharge are not accurate. A new model of recharge is formulated that is consistent with the unique geologic framework in the basin. In the area of study, the Rio Grande flows across a broad alluvial floodplain, the “El Paso-Juarez Vall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…More recent water samples collected for the analysis of possible groundwater salinity bias are documented in Dadakis (2004), Hibbs and Merino (2006), Merino (2006), Hibbs and Merino (2020) and Eastoe et al (2022) [41,[57][58][59][60], and in our other unpublished data developed during sampling campaigns between 2003 and 2022. These samples were collected from water wells, springs, agricultural drains, and the Rio Grande.…”
Section: Methodsmentioning
confidence: 84%
“…More recent water samples collected for the analysis of possible groundwater salinity bias are documented in Dadakis (2004), Hibbs and Merino (2006), Merino (2006), Hibbs and Merino (2020) and Eastoe et al (2022) [41,[57][58][59][60], and in our other unpublished data developed during sampling campaigns between 2003 and 2022. These samples were collected from water wells, springs, agricultural drains, and the Rio Grande.…”
Section: Methodsmentioning
confidence: 84%
“…Studies of stable O and H isotopes showed that the Rio Grande surface water follows a single, clearly-defined evaporation trend from the river source in Colorado to the Hueco Bolsón [14]. Groundwater recharged by the river is therefore readily distinguished from native Hueco Bolsón recharge [19,[34][35][36]. Native groundwater plots along the global meteoric water line, GMWL [37] or along evaporation trends different from those of the river.…”
Section: Previous Isotope Studies Hueco Bolsónmentioning
confidence: 99%